Found in translation: The role of response mappings for observing binding effects in localization tasks. Issue 8 (14th September 2022) - Schöpper, Lars-Michael; Lappe, Markus; Frings, Christian
ABSTRACT: According to action control theories, response and stimulus' features are integrated into event files. Repeating any of an event file's components retrieves the previously bound information, causing benefits for full repetition, but interference for partial repetition. Yet, such "binding effects" are absent in localization performance. By assuming sequential processing steps until response execution as assumed in visual search, we hypothesized that, for localization, participants can execute their response without the need to process target features. Hence, post-selective processing might be crucial for binding effects to emerge. Here, participants localized coloured targets appearing on one of four corners of a touchpad in two response conditions, namely, directly tapping on the target (direct response mapping), and tapping on the corner diagonal opposite to the target (translational response mapping). Only the translational response mapping yielded binding effects between localization response and colour. The direct response mapping instead showed an effect that is better explained by (non-spatial) Inhibition of Return or related change benefit effects. We conclude that an arbitrary response mapping – based on a translation of a spatial feature into a non-direct spatial response – can lead to binding effects even in localization tasks.